CONTEXTUAL TEACHING AND LEARNING UNTUK PENINGKATAN KETERAMPILAN MENULIS NARASI SISWA KELAS IV SEKOLAH DASAR - Triaji, Choirudin Lutfi; Yayuk, Erna; Fithriyanasari, Elly (Universitas Muria Kudus, 2019)
The purpose of the study is knowing the increase of students' skills in writing narrative texts through learning activities with the contextual teaching and learning model in class IV A at Kauman 1 Malang Elementary School. Field data shows that students still write with that tend not to be coherent, short stories, and wrong in using PUEBI. This study uses the PTK method (Classroom Action Research). The research subjects were 31 students of class IV A SDN Kauman 1 Malang. The research was conducted in two cycles. Data collection uses tests and observations.The results of the study were obtained from student observations when learning activities and narrative text writing tests. The data analysis used in this study are two, qualitative descriptive and quantitative descriptive.Cycle I shows that students' skills in writing narrative texts have increased from pre-cycle test results with a class average value of 71.97 increasing to 73.84 on the results of cycle I and 77.87 tests on cycle II test results with the percentage of students completing in one class starting at 35.48% on the pre-cycle test results to 51.61% on the results of the first cycle test and 74.19% on the results of the cycle II test. The conclusion of this study is contextual teaching and learning can be used to improve students' narrative text writing skills.